Angle-side properties of polygons inscribable in an ellipse. Issue 7 (1st June 2022) - Jahangiri, Jay; Segal, Ruti; Stupel, Moshe
Abstract : We consider polygons that are inscribable in an ellipse and as special cases in a circle. We explore the angle-side properties of such polygons, give counterexamples for certain circumstances, and give instructions for constructing such cyclic polygons.